Pembuatan Media Interaktif untuk Anak Usia Balita Belajar Membaca - Wibawa, Satriya Gede Jaya; Budhi, Gregorius Satia; Dewi, Lily Puspa (Jurnal Infra, 2015)
Making this program aims to interest children in learning to read in a fun way, so that children in the age of the children can master the technique of reading. This is done because of demands for children aged under five are expected to master the technique of reading before they continue their education at the elementary level, but because reading is a basic foundation in communication.For application design researchers using interviews with informants, as well as the selection of the manufacturing features in interactive media.The results of this interactive medium is a game that has two menus is "Start and Quiz", while the material created in this game consists of the introduction of the alphabet as well as the introduction of one to three syllables. The test results of the game is, this game can support and assist in the learning process among teachers, parents and students to read. And these games has an interesting view and in accordance with what they have learned at school, so as to attract the students to use.